Ionizing radiation exposure of stem cell-derived chondrocytes affects their gene and microRNA expression profiles and cytokine production - Ewelina Stelcer (Nature Portfolio, 2021)
Abstract Human induced pluripotent stem cells (hiPSCs) can be differentiated into chondrocyte-like cells. However, implantation of these cells is not without risk given that those transplanted cells may one day undergo ionizing radiation (IR) in patients who develop cancer. We aimed to evaluate the effect of IR on chondrocyte-like cells differentiated from hiPSCs by determining their gene and microRNA expression profile and proteomic analysis. Chondrocyte-like cells differentiated from hiPSCs were placed in a purpose-designed phantom to model laryngeal cancer and irradiated with 1, 2, or 3 Gy. High-throughput analyses were performed to determine the gene and microRNA expression profile based on microarrays. The composition of the medium was also analyzed. The following essential biological processes were activated in these hiPSC-derived chondrocytes after IR: "apoptotic process", "cellular response to DNA damage stimulus", and "regulation of programmed cell death". These findings show the microRNAs that are primarily responsible for controlling the genes of the biological processes described above. We also detected changes in the secretion level of specific cytokines. This study demonstrates that IR activates DNA damage response mechanisms in differentiated cells and that the level of activation is a function of the radiation dose.